1978
DOI: 10.1288/00005537-197811000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical consequences of CO2 laser surgery of the guinea pig ear

Abstract: A modified American Optical (Model 100) CO2 laser was used to produce lesions in the tympanic membranes, ossicles, and cochlear capsules of guinea pigs. Even with the lowest available intensities and durations (0.4 watts, 50 msec), there was damage to the inner ear. Although laser surgery of the ear can avoid mechanical trauma and bleeding as well as increase accuracy, the use of commercial lasers in ear surgery should be avoided until a proven unit is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Wilpizeski was the first to use the microsurgical CO 2 laser for making perforations in the tympanic membrane of the squirrel monkey 6 . He performed partial myringectomies by vaporizing the posterior quadrant of the tympanic membrane in 40 monkeys and found that all perforations “healed quickly.” Lyons et al used a modified CO 2 laser with an AC power supply that consistently caused damage to inner ear structures in the guinea pig 8 . Even at low power settings and short exposure times the laser application was too unpredictable to warrant continued use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilpizeski was the first to use the microsurgical CO 2 laser for making perforations in the tympanic membrane of the squirrel monkey 6 . He performed partial myringectomies by vaporizing the posterior quadrant of the tympanic membrane in 40 monkeys and found that all perforations “healed quickly.” Lyons et al used a modified CO 2 laser with an AC power supply that consistently caused damage to inner ear structures in the guinea pig 8 . Even at low power settings and short exposure times the laser application was too unpredictable to warrant continued use.…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong initially believed that 2 to 3 weeks was sufficient 4 . To create a tympanostomy that will remain open for several weeks, the CO 2 laser can be used to vaporize an opening in the tympanic membrane without inserting a PE tube 5‐10 …”
Section: Introductionmentioning
confidence: 99%
“…The required period of time for ventilation of the middle ear mucosa healing provided with incisional myringotomy is shorter and the period provided with ventilation tubes is longer than expected [1,5,6]. Lyons et al [8], made lesions on the tympanic membranes, middle ear ossicles and cochlear capsules of the guinea pigs by using CO 2 laser, and set forth that even minimal power and time settings, such as 0.4 W and 50 ms, injures the inner ear and suggested that CO 2 laser not to be used in otologic surgery, unless it was found to be safe.…”
Section: Discussionmentioning
confidence: 99%
“…Laser myringotomy is not a new idea. Lyons et al 14 experimented with CO 2 lasers in guinea pig ears in 1978, creating controlled ossicular and cochlear lesions. In 1982 Goode 15 reported the first laser myringotomies in humans and described prolonged middle ear ventilation when compared with incisional myringotomy.…”
Section: Discussionmentioning
confidence: 99%